A Cause for Alarm: Increasing Translocation Success of Captive Individuals Through Alarm Communication - Morris, Vanessa; Pitcher, Benjamin James; Chariton, Anthony (Frontiers in Conservation Science, 2021)
Translocation programmes implying the movement of animals from one place to another aim to sustain endangered populations in the wild. However, their success varies greatly, with predation being a major contributing factor. This is particularly prevalent in released captive-raised individuals which have a reduced or lost awareness of predators. Alarm calls are an immediate response made towards a predator, mostly studied in highly predated, social vertebrates. These warning vocalisations are a vital part of a prey species’ anti-predator behaviour, enhancing the individuals’ and surrounding listeners’ survival. To date, most translocation programmes have not considered this behaviour for release success. Here we review the literature, summarising alarm communication systems of wild and captive vertebrates, aiming to establish recommendations and actions which could encourage alarm communication behaviour in captive vertebrate species. Observations of wild animals show that alarm-call understanding is gained through the experience of predation pressure from a young age, amongst conspecific and heterospecific social groups, which captive individuals can lack. This information, combined with consideration of a programme’s accessible resources and captive individual’s developmental history, is pivotal to efficiently guide appropriate actions. Focusing on preserving behaviours in captivity, we provide a list of recommendations and actions to guide the reinforcement of alarm communication throughout the translocation process. Ensuring predator awareness and the maintenance of alarm communication in translocated individuals may greatly improve the likelihood of release success.